The effects of objectification on stereotypical perception and attractiveness of women and men - Rollero Chiara; Tartaglia Stefano (Psihologija, 2016)
Objectification has been found to have negative consequences on how women are perceived by others. However in an even more sexualized world being a sexual object has become a standard of physical attractiveness for women and objectification could foster a positive evaluation increasing attractiveness. Although Objectification Theory was originally grounded in women’s experiences, some research points to the promise of Objectification Theory for understanding men’s experiences as well. The aim of the paper was investigating the effects of objectification on gender stereotypes and perceived attractiveness. Two experimental studies were conducted. Study 1 (N=139) investigated the effects of objectification on female targets. Study 2 (N=146) investigated the effects on male targets. In both studies three dependent variables were considered: communality, agency, and attractiveness. Results of Study 1 revealed that objectified women were considered less communal and more attractive. Moreover, men perceived objectified women less agentic than the non-objectified ones, whereas women showed the opposite perception. Concerning men, objectification has a limited impact, as it interacted with participants’ gender only on communality: men considered objectified males more communal than the non-objectified ones, while women revealed the opposite perception.